Development and Optimization of Hydrophilic Matrix Based Molnupiravir Sustained Release Dosage Formulation using Full Factorial Design (Dhaka University Journal of Pharmaceutical Sciences, 2025)
Molnupiravir, an orally administered antiviral drug originally developed for influenza but not approved, inhibits the replication of SARS-CoV-2 and has been repurposed as an antiviral treatment for COVID-19. This research aimed to develop 400 mg sustained release tablets of molnupiravir for a dosage regimen of two tablets every 12 hours using design of experiment (DoE) approach. The study utilized 32 full factorial design, implemented through the use of Design Expert® software. The formulation was optimized using methocel® K15M and povidone K30 as independent variables, with drug release at 2, 8 and 12 h in pH 6.8 phosphate buffer as the dependent variables. An optimal formulation was identified through statistical analysis and empirical evaluation, requiring 6.84% methocel® K15M and 4.27% povidone K30. The sustained release tablets of molnupiravir exhibited release kinetics consistent with the Hixson-Crowell model. The results of this study allowed us to suggest a new tablet dosage form of molnupiravir, with the objective of enhancing both efficacy and adherence in the treatment of COVID-19.Dhaka Univ. J. Pharm. Sci. 24(1): 67-75, 2025 (June)